Z problematyki umorzenia konsensualnego - Kania, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The purpose of the article is to discuss the institution of consensual discontinuation of proceedings, in force since 1 July 2015 Article 59a of the Penal Code. The study focuses in particular on the legal character of this solution and implications of the codex allowing for its application. For this reason, statutory conditions were analyzed, related to a the violator, b the act committed by the violator, c victim’s behaviour, d limitations regarding the possibility to use the discussed institution.
Keywords: cele kary; wniosek ofiary; pojednanie sprawcy i ofiary; kontznuacja porozumienia